Linking individual and group motives for violent conflict - Matthew Nanes (Research & Politics, 2021)
Research on the role of grievances in civil conflict is surprisingly inconclusive, with well-cited studies disagreeing on the relationship between perceived deprivation and violence. I argue that the role of grievances depends on an interaction between individual and group-level incentives. Individuals who perceive themselves as personally deprived are more likely to support or participate in anti-regime violence, but only if a successful rebellion would enhance their group’s power relative to the status quo. I test this argument in the context of Iraq’s sectarian civil war using data from a 2016 survey of 800 Baghdad residents. Using a list experiment to measure individuals’ willingness to consider violence against a government they feel is ignoring their needs, I find that minority Sunnis who are economically dissatisfied are significantly more willing to consider violence than similarly aggrieved Shias. However, as economic satisfaction increases, Sunnis’ propensity for violence decreases until it becomes indistinguishable from Shias’ propensity. These results clarify the joint impacts of vertical and horizontal grievances. Group inequality and individual deprivation are each necessary but not sufficient to fully explain individuals’ propensities for anti-state violence.